The main stages of foundation of the social work in the USA - Тименко, В.М. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2012)
There were examined the main stages of foundation of the social work in the USA from the beginning of the 20th centaury till nowadays. There was made analysis of the main scientific trends, personalizes, witch influenced to the theory and practice of the social work in the USA during the 20th centaury, and also there was made an attempt of giving periods to the development of the social work in the USA.